Rapid, direct effects of statin treatment on arterial redox state and nitric oxide bioavailability in human atherosclerosis via tetrahydrobiopterin- mediated endothelial nitric oxide synthase coupling - Antoniades, C; Bakogiannis, C; Leeson, P; Guzik, T; Zhang, M; Tousoulis, D; Antonopoulos, A; Demosthenous, M; Marinou, K; Hale, A; Paschalis, A; Psarros, C; et al. (2011)
Background-: Treatment with statins improves clinical outcome, but the exact mechanisms of pleiotropic statin effects on vascular function in human atherosclerosis remain unclear. We examined the direct effects of atorvastatin on tetrahydrobiopterin-mediated endothelial nitric oxide (NO) synthase coupling in patients with coronary artery disease. Methods and Results-: We first examined the association of statin treatment with vascular NO bioavailability and arterial superoxide (O2.-) in 492 patients undergoing coronary artery bypass graft surgery. Then, 42 statin-naïve patients undergoing elective coronary artery bypass graft surgery were randomized to atorvastatin 40 mg/d or placebo for 3 days before surgery to examine the impact of atorvastatin on endothelial function and O2.- generation in internal mammary arteries. Finally, segments of internal mammary arteries from 26 patients were used in ex vivo experiments to evaluate the statin-dependent mechanisms regulating the vascular redox state. Statin treatment was associated with improved vascular NO bioavailability and reduced O2.- generation in internal mammary arteries. Oral atorvastatin increased vascular tetrahydrobiopterin bioavailability and reduced basal and N-nitro-L-arginine methyl ester-inhibitable O2.- in internal mammary arteries independently of low-density lipoprotein lowering. In ex vivo experiments, atorvastatin rapidly improved vascular tetrahydrobiopterin bioavailability by upregulating GTP-cyclohydrolase I gene expression and activity, resulting in improved endothelial NO synthase coupling and reduced vascular O2.-. These effects were reversed by mevalonate, indicating a direct effect of vascular hydroxymethylglutaryl- coenzyme A reductase inhibition. Conclusions-: This study demonstrates for the first time in humans the direct effects of statin treatment on the vascular wall, supporting the notion that this effect is independent of low-density lipoprotein lowering. Atorvastatin directly improves vascular NO bioavailability and reduces vascular O2.- through tetrahydrobiopterin- mediated endothelial NO synthase coupling. These findings provide new insights into the mechanisms mediating the beneficial vascular effects of statins in humans. Clinical Trial Registration-: URL: http://www.clinicaltrials.gov. Unique identifier: NCT01013103. © 2011 American Heart Association, Inc.